Exploring menstrual hygiene management practices among displaced coastal women in Kerala, India - Jessy Prabhakar; Aswin MG; Asmi Fathima Nazar; Adarsh MS; Jibin Job PJ; Nisam AP; Krishna Priya MJ; Mini GK (The Journal of Climate Change and Health)
Introduction: During climate related displacement, women face additional challenges in safely managing menstrual hygiene. The aim of this study is to evaluate menstrual hygiene management practices among displaced women of reproductive age in the coastal areas of Kerala, India. Materials and Methods: A cross-sectional study was conducted among displaced costal women in Kerala. We collected data on their socio-demographic factors, WaSH facilities, and menstrual hygiene practices following displacement, using a pre-tested semi-structured interview questionnaire. The participants also completed the Menstrual Hygiene Practice Needs Scale. We performed both univariate and bivariate analyses. Results: The average age of the participants was 32 years (SD±8.5). Around 59 % had completed some school education, 41 % had completed college education, 30 % were employed, and 59 % belonged to lower socioeconomic status. Over half of the participants had poor menstrual hygiene practices (55 %). Older women (OR:1.72, 95 % CI:1.08–2.72) and those with lower education (OR:2.22, 95 % CI:1.38–3.56) were more likely to have poor menstrual hygiene practices. Disposal of menstrual materials is problematic. Self-reported physician-diagnosed urinary tract infection (UTI) was 46 %, and reproductive tract infection was 8.4 %. Conclusion: The research highlights the need to improve menstrual hygiene practices and address UTI prevalence through better facilities during sea invasions. Collaboration with local authorities to address related concerns is recommended.